Innovative Solutions for Improving the Ecological Parameters of Combustion and Electric Vehicles – On the Example of Artificial Intelligence and Modification of The Power Supply System - Karol F. ABRAMEK; Tomasz OSIPOWICZ; Łukasz MOZGA; Konrad Prajwowski; Jaromir MYSŁOWSKI (Communications of International Proceedings, 2021)
In today's automotive market, major manufacturers agree that the era of combustion vehicles is slowly coming to an end, and the future will belong to zero-emission vehicles. It is apparent that this process will take the character of gradual changes. In the first place, their goal will be to decarbonise conventional power units, and at a later stage, those using electricity for propulsion. This paper presents considerations on the possibility of improving the ecological parameters of both combustion and electric vehicles. An innovative approach was proposed in the field of individual technological solutions, the aim of which is to improve the ecological parameters of both types of drives. In the case of the electric vehicle, innovation is based on a battery capacity and energy management system, supported by artificial intelligence. In the case of a combustion vehicle, innovation is based on modifications of the fuel supply system. The presented research may be helpful in answering the question of how the development path of modern vehicles will proceed in the era of zero-emissions. In addition, the presented results can provide a basis and incentive for further research into innovative solutions for improving the environmental performance of both combustion and electric vehicles.
Keywords: Innovation; Technological Solutions; Road Transport; Artificial Intelligence; System Modification.